Os limites constitucionais à prevalência do negociado sobre o legislado perante a reforma trabalhista (Lei 13.467/2017) - Bruxel, Charles da Costa (2021)
The general objective of the scientific work is to analyze and define the constitutional limits to the validity of collective bargaining that may, in its content, come into conflict with the rights provided for in the Federal Constitution and in the ordinary legislation and to investigate the compatibility of these limits with the normatization on the matter stipulated by Law 13.467/2017 (Brazilian Labor Reform Law). The specific objectives of this dissertation, on the other hand, are: to define the constitutional limits to the validity of collective bargaining that come into conflict with the rights provided for in the Federal Constitution and in the ordinary legislation; to establish the appropriate interpretation to be given to the norms given by Law 13.467/2017, which aims to clarify in which matters collective bargaining may or may not prevail over the legislated law; to analyze the constitutionality of the forecasts contained in Law 13.467/2017 that aim to elucidate on which themes collective bargaining may or may not prevail over the law legislated. The research is classified as basic, qualitative, explanatory, bibliographic and documentary and follows, predominantly, the deductive method of scientific approach. Having tested the hypotheses and carried out the analyzes, it was concluded, in summary, that: the criterion of the Most Favorable Worker Rule is not sufficient to resolve the content conflict between the negotiated and the legislated; the Federal Constitution imposes stricter limits for the flexibility of the “minimum legal provisions for protection of work”, but nonetheless it establishes restrictions, albeit more lenient, on the reduction or suppression of the legislated law not included in this notion; Law 13.467/2017 presents several unconstitutional provisions, but, despite this, most of the rules that deal with collective bargaining are clearly compatible with the Federal Constitution or at least can be interpreted in line with the Federal Constitution. Finally, the adopted methodology proved to be satisfactory, and it was possible to achieve, in depth, the programmed objectives.